FAKTOR PENYEBAB KURANGNYAMINAT GENERASI MUDA PADA TRADISI BERZANJI DIDAIK KABUPATEN LINGGAPROVINSI KEPULAUANRIAU - Fatma Lingga Tari; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the lack of interest in the younger generation of the Berzanji tradition which will lead to drastic extinctions, lack of curiosity will cause various symptoms such as lack of knowledge of the Daik tradition. So the authors take the title of the research "Factors Causing the Lack of Interest of Young Generation Interest in the Adoration of Promising in Daik Lingga Regency, Riau Islands Province" The formulation of the problem in this study is what factors cause the lack of interest of the Young Generation in the Adoration Tradition in Daik Lingga Regency, Riau Islands Province? The purpose of this study was to determine the factors causing the lack of interest of the younger generation in the tradition of Adoration in Daik Lingga Regency, Riau Islands Province. This research is qualitative. Data collection techniques in this study are, observation, interview and documentation. There are 10 informants in this study are Religious Leaders, LAM Chairperson, Members of Promise, and Youth GenerationKeyWords: Lack of Interest in Young Genarasi in the Promised Tradition.